ANALISIS GAYA DORONG (THRUST) PROPELLER PADA PESAWAT MODEL REMOTE CONTROL (UAV) - Sihaan, Josua Cornel Roni; Munawir, Al; Husin, Zakir (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
Unmanned aircraft or known as UAV (Unmanned Aerial Vehicle) is an aircraft technology that is controlled ly by the operator using  Control. The thrust is determined according to the needs of the aircraft itself. This study uses a thrust test stand that uses a mass measuring device as a measuring force, using a brushless motor and 3 different types of propellers, namely propeller two with a size of 8 x 4 inches and 10 x 7 inches, three propellers with a size of 6 x 3 inc to determine the optimal thrust for missions flying -controlled model aircraft (UAV). After testing, it was found that the smallest thrust force of the 6x3 inch blade type propeller, on this type of propeller only 3,874 N of thrust is produced at 100% throttle percentage and uses a 3 cell battery. While the greatest thrust generated from the propeller with a type of two when 10x7 inches, on this propeller and using a 4 cell battery can produce a Thrust of 13,194 N with a percentage of full throttle or 100%. The thrust required for the aircraft to fly cruising in the air is 0.806 N, while the thrust required for the aircraft to take off is 6.513 N.Keywords: Control Model Aircraft, Propeller, Thrust